[Untitled] - Cantrell, Jonathan Thomas (2012)
This thesis defense and accompanying thesis exhibition is an investigation of cultural myths about race, gender and sexuality. The body is used as a familiar form to which metaphorical elements are added. These elements are combined in a way that creates the kind of cognitive dissonance that cultural myths are meant to reconcile, which, in turn exposes those myths and biases. The exhibition includes five life-size charcoal figure drawings. The drawings are rendered in a style that is influenced by classical techniques. The artists such as Rembrandt van Rijn and Michelangelo Merisi de Caravaggio influence the way I model the form. Other, more contemporary, influential artists include Egon Schiele, Odd Nerdrum and Luis Caballero whose work informed these figures both technically and conceptually. It is all these artists which are my foundation of the use of the body as a tool for conversations of the human condition. The theoretical scaffolding that this exhibit is based on includes the writings of Jean-Paul Sartre, Frantz Fanon, Gilles Deleuze and Felix Guattari.